Gr‐1highCD11b+ Cells Suppress B Cell Differentiation and Lupus‐like Disease in Lupus‐Prone Male Mice. Issue 9 (26th August 2013) - Trigunaite, Abhishek; Khan, Ayesha; Der, Evan; Song, Anne; Varikuti, Sanjay; J⊘rgensen, Trine N.
Abstract : Objective: Systemic lupus erythematosus (SLE) develops much more readily in females than in males. Previous research has focused primarily on identifying mechanisms pertinent to the pathology in females. The aim of the current study was to delineate active protective mechanisms in males. We present evidence of a new male‐associated mechanism of protection against the development of lupus‐like disease in lupus‐prone (NZB × NZW)F1 mice. Methods: We identified previously uncharacterized cellular and functional differences in myeloid cells between male and female (NZB × NZW)F1 mice, with the use of flow cytometry, confocal imaging, in vivo antibody‐mediated depletion, and in vitro cell coculture assays. Results: A population of Gr‐1 high Ly‐6G+CD11b+ myeloid cells was found to be constitutively increased in male (NZB × NZW)F1 mice as compared with female mice and was regulated by testosterone. The cells were located adjacent to spleen B cell follicles in vivo and were found to directly inhibit cytokine‐induced differentiation of naive B cells into antibody‐secreting cells in vitro. Most notably, treatment with anti–Gr‐1–depleting antibodies increased the spontaneous production of antinuclear autoantibodies in male (NZB × NZW)F1 mice, while a similar approach in female mice had no effect on disease development. Conclusion: Male lupus‐prone (NZB × NZW)F1 mice harbor elevated levels of a population of myeloid cells with pronounced immunosuppressive capacities that specifically target B cells and the production of antibodies in vivo. We suggest that these cells represent a male‐driven inhibitory mechanism involved in the control of B cell pathogenesis, delaying (or preventing) lupus‐like disease development in otherwise genetically predisposed male (NZB × NZW)F1 mice.